SOCIAL LOAFING PADA ORGANISASI MAHASISWA: PERAN KOHESIVITAS KELOMPOK DAN SELF-EFFICACY - Akbar, Jepri; Wibowo, Danan Satriyo; Widyarini, Nurlaela (Universitas Gunadarma, 2024)
Social loafing often emerges in organizational activities characterized by a decrease in active participation of members in preparing and implementing programs, as well as members' tendency to be passive in discussion forums and avoid tasks. This behavior has negative impacts not only on organizational effectiveness but also on the well-being of the individuals involved. The research aims to investigate the influence of group cohesion and self-efficacy on social loafing behavior among student organization members. The research design is a quantitative correlational study. The subjects consist of 159 members of the Muhammadiyah Student Association (IMM) Branch in Jember using a cluster sampling technique. The researcher employed the Social Loafing Tendency Questionnaire to measure social loafing, the Group Environment Questionnaire to measure group cohesion, and General Self-efficacy to measure self-efficacy. The data analysis technique used multiple regression analysis. The research findings indicate a significant influence of group cohesion and self-efficacy on social loafing among student organization members (F= 44.642; p < 0.05), meaning that higher group cohesion and self-efficacy lead to increased tendencies of social loafing. The results also show that group cohesion has a significant negative relationship with social loafing (t = -8.860; p < 0.05), while self-efficacy does not influence social loafing (t = -1.924; p > 0.05). Suggestions for future research include considering the specific context of the organization to be studied, such as the tasks to be measured, culture, organizational structure, and leadership.